2017
DOI: 10.1007/s11242-017-0901-5
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Wicking Process in Textiles

Abstract: We investigate wicking in textiles using neutron radiography on fabrics of two types, woven and simple jersey knit, and made of yarns of four different materials: cotton, polyethylene terephthalate, polyamide and polypropylene. Moisture distribution in the samples is quantified from the images, and the total mass is compared with gravimetric measurements for validation. The position of the front versus time is obtained from segmented neutron images and backlight images, with good agreement between the two meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 34 publications
1
37
0
Order By: Relevance
“…The curve is divided into two parts, describing the fabric from imbibition to evaporation: Phase I, unsteady wicking and evaporation in the initial 10 min with water transfer speed S 1 ; Phase II, steady wicking-evaporating from 10 to 120 min with water transfer speed S 2 . The whole observed process is in good accordance with that in previous research [7,21].…”
Section: The Wicking-evaporating Behaviorsupporting
confidence: 91%
See 2 more Smart Citations
“…The curve is divided into two parts, describing the fabric from imbibition to evaporation: Phase I, unsteady wicking and evaporation in the initial 10 min with water transfer speed S 1 ; Phase II, steady wicking-evaporating from 10 to 120 min with water transfer speed S 2 . The whole observed process is in good accordance with that in previous research [7,21].…”
Section: The Wicking-evaporating Behaviorsupporting
confidence: 91%
“…As a widely used wicking measurement method, the strip vertical wicking test was first proposed by Ghali [6]. Previous studies focused mostly on physical models [7,8] and measurements [9,10] of wicking behavior in yarn and textiles and took the maximum wicking height/distance as a key moisture transfer index [11][12][13][14][15][16][17][18]. It was previously observed that wicking and evaporation occur simultaneously when a fabric is partly immersed in water [19] as illustrated in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spontaneous imbibition, where a nonwetting fluid is displaced by a wetting fluid by capillary forces, in porous media is a common phenomenon encountered in many scientific and engineering processes (C. Li et al., 2019; Meng et al., 2017; C. Z. Qin & van Brummelen, 2019; Schmid & Geiger, 2012), such as oil recovery (Morrow & Mason, 2001; Y. Yang et al., 2019), filtration in soil (Kao & Hunt, 1996), wicking in textiles (Parada, Derome, et al., 2017; Parada, Vontobel, et al., 2017) or paper‐like materials (Z. Liu et al., 2018), and so on. In order to analyze the underlying mechanisms of spontaneous imbibition, porous media are usually simplified such that they consist of regular shaped capillaries (Cai et al., 2014), including cylindrical and angular tubes.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1–3 ] For example, commercial moisture‐wicking textiles have attracted tremendous attention because of their ability to cool the human skin by extracting the excessive sweat, through water transport and heat dissipation. [ 4,5 ] These textiles have been extensively studied and possess a strong capillary force inside the inter‐fiber channel which extracts the sweat rapidly from the skin to the outer environment for fast evaporation, such as the Coolmax fabric composed of profiled fibers [ 6,7 ] and directional water transport fabric with asymmetric wettability. [ 8–11 ] However, limited progress has been made in improving heat dissipation during sweat release, which can lead to heat stress during perspiration, especially in the hot and humid environment.…”
Section: Introductionmentioning
confidence: 99%